Factors That Influence NICU Health Care Professionals' Decision Making to Implement Family-Centered Care. (February 2022) - Vittner, Dorothy; DeMeo, Stephen; Vallely, Jaxon; Parker, Mary; Baxter, Anna; McGrath, Jacqueline
Abstract : Background: Neonatal intensive care unit (NICU) is a multifaceted, technology-driven high stress environment for professionals, infants and families. Purpose: Examine healthcare professionals' beliefs and perceptions regarding providing FCC within the context of NICU. Methods: This exploratory descriptive study used an online-survey format. The survey comprised several instruments including the Perceived Stress Scale, symptoms of burnout subscale from the Professional Quality of Life scale, and the Family Nurse Caring Belief Scale (FNCBS). Demographic and open-ended items were also included. Results: Sample consisted of 115 multidisciplinary participants working in a level IV neonatal intensive care unit. Participants report strong levels of FCC beliefs. Participants strongly agreed (82%) or agreed (18%) that no matter how sick the infant is, he or she needs to be treated as an individual . A significant correlation ( r =−0.343, P < .001) exists between participant's stress composite score and FNCBS composite score. There were significant relationships between participant's years of experience ( F = 5.35, P < .002) and education levels ( F = 2.60, P < .05) and higher FNCBS composite scores. There were also significant relationships between participant's years of experience ( F = 4.77, P < .004) and education ( F = 2.89, P < .039) with higher Perceived Stress Scale composite scores. Implications for Practice: Results suggest that while participants agreed that FCC is important, they also believed that inadequate staffing and inappropriate assignments may lead to rationing of care. Implications for Research: Further research is needed to explore factors that lead to rationing of FCC.